Impact of comorbidities on atrial fibrillation and sudden cardiac death in hypertrophic cardiomyopathy. (8th December 2021) - Sridharan, Aadhavi; Maron, Martin S.; Carrick, Richard T.; Madias, Christopher A.; Huang, Dou; Cooper, Craig; Drummond, Jennifer; Maron, Barry J.; Rowin, Ethan J.
Abstract: Background: The impact of comorbid disease states on the development of atrial and ventricular arrhythmias in patients with hypertrophic cardiomyopathy (HCM) remains unresolved. Objective: Evaluate the association of comorbidities linked to arrhythmias in other cardiovascular diseases (e.g., obesity, systemic hypertension, diabetes, obstructive sleep apnea, renal disorders, tobacco, and alcohol use) to atrial fibrillation (AF) and sudden cardiac death (SCD) events in a large cohort of HCM patients. Methods: A total  of 2269 patients, 54 ± 15 years of age, 1392 males, were evaluated at the Tufts HCM Institute between 2004 and 2018 and followed for an average of 4 ± 3 years for new‐onset clinical AF and SCD events (appropriate defibrillation for ventricular tachyarrhythmias, resuscitated cardiac arrest, or SCD). Results: One or more comorbidity was present in 75% of HCM patients, including 50% with ≥2 comorbidities, most commonly obesity (body mass index [BMI] ≥ 30 kg/m 2 ) in 43%. New‐onset atrial fibrillation developed in 11% of our cohort (2.6%/year). On univariate analysis, obesity was associated with a 1.7‐fold increased risk for AF ( p  = .03) with 12% of obese patients developing AF (3.3%/year) as compared to 7% of patients with BMI < 25 kg/m 2 (1.6%/year; p  = .006). On multivariate analysis, age and LA transverse dimension emerged as the only variables predictive of AF. Comorbidities, including obesity, were not independently associated with AF development ( p  > .10 for each). SCD events occurred in 3.3% of patients (0.8%/year) and neither obesity nor other comorbidities were associated with increased risk for SCD ( p  > .10 for each). Conclusions: In adult HCM patients comorbidities do not appear to impact AF or SCD risk. Therefore, for most patients with HCM, adverse disease related events of AF and SCD appear to be primarily driven by underlying left ventricular and atrial myopathy as opposed to comorbidities.